2006
DOI: 10.1002/dc.20503
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic diagnosis of pancreatic endocrine tumors by endoscopic ultrasound‐guided fine‐needle aspiration: A review

Abstract: Precise localization and diagnosis of pancreatic endocrine tumors (PETs) is important, because pancreatic PETs have different clinical and biological behavior and treatment modalities than do exocrine pancreatic tumors. In contrast to the much more common exocrine adenocarcinomas, cytologic studies of PET are relatively rare and many cytopathologists lack experience with the cytomorphologic features of these tumors.During the last 10 yr, endoscopic ultrasound (EUS)-guided fine-needle aspiration (FNA) has matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 69 publications
0
45
0
2
Order By: Relevance
“…Imaging techniques such as transabdominal ultrasound, CT, or MRI, are typically used to localize insulinomas. Studies have shown that detection of pNETs using conventional imaging is dependent on the lesion size, with detection rates less than 10% for tumors smaller than 1 cm in diameter, 30-40% for tumors 1-3 cm in diameter, and greater than 50% for those larger than 3 cm in diameter 4 . Insulinomas have been inconsistently localized by conventional imaging compared to other pNETs because they are relatively smaller at the time of diagnosis, with 90% measuring less than 2 cm in diameter 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging techniques such as transabdominal ultrasound, CT, or MRI, are typically used to localize insulinomas. Studies have shown that detection of pNETs using conventional imaging is dependent on the lesion size, with detection rates less than 10% for tumors smaller than 1 cm in diameter, 30-40% for tumors 1-3 cm in diameter, and greater than 50% for those larger than 3 cm in diameter 4 . Insulinomas have been inconsistently localized by conventional imaging compared to other pNETs because they are relatively smaller at the time of diagnosis, with 90% measuring less than 2 cm in diameter 11 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to often being more reliable in the detection and localization of insulinomas compared to conventional imaging, EUS also uniquely allows for diagnostic material to be obtained in a safe and minimally invasive manner via FNA, can aid surgical resection by preoperatively tattooing an otherwise undetected insulinoma, and has shown therapeutic potential via ultrasound guided ethanol ablation 4,10,13 . Further, EUS as a method of preoperative localization of pancreatic neuroendocrine tumors is cost effective.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed that FNA can be used to accurately diagnose PancNET in most cases. A review of the literature 2,[14][15][16][17][18][19][20] shows that FNA compares favorably with core biopsies because the latter are technically more difficult, especially with smaller lesions, and also more limited in their capacity to sample the tumor. Only 3 cases during the time frame of this study were complicated by patient discomfort or hemorrhage, and all of them were during the era of the percutaneous approach.…”
Section: Follow-upmentioning
confidence: 99%
“…This low incidence of complications is along the lines reported by others and partly explains why FNA, especially EUS-FNA, has become the gold standard relative to core biopsies. 2,[14][15][16][17][18][19][20] The establishment of a correct diagnosis using FNA, when combined with the localization and staging that can be achieved through medical imaging, provides important information in the preoperative evaluation and management of these patients. For example, nonfunctional PancNETs confined to pancreas in the elderly are appropriately considered for observational management with periodic cross-sectional imaging instead of surgical intervention.…”
Section: Follow-upmentioning
confidence: 99%
“…For example, a CT sensitivity of 94% using multidetector scanning and fine reformats has been demonstrated (13), while MRI sensitivities have been described of 79% for delayed enhanced T1-weighted images (14) or with the use of combined sequences up to 85% (15). Endoscopic ultrasound (EUS) is evolving and improving, and may provide an opportunity for histological diagnosis, but this semi-invasive technique is highly dependent on operator experience (16,17). Selective intra-arterial injection of the pancreatic arteries with calcium and hepatic venous sampling for insulin, first introduced 17 years ago (18), correlates anatomy with function, and in many series, it appears to be the most sensitive method for regionalisation of insulinoma.…”
Section: Introductionmentioning
confidence: 99%